Open the box: A behavioural perspective on the reshoring decision-making and implementation process. Issue 3 (June 2020) - Boffelli, Albachiara; Golini, Ruggero; Orzes, Guido; Dotti, Stefano
Abstract: In the realm of manufacturing location decisions, reshoring has increasingly attracted the attention of practitioners, policy makers and scholars. While many articles have analysed the drivers of reshoring decisions, the decision-making and implementation process still lacks empirical analyses. This paper addresses this gap with a grounded theory approach, in particular, through an iterative process going back and forth between the theoretical and empirical worlds. By analysing four cases from the textile-clothing-leather-footwear industry, we demonstrate that the process characteristics are affected by the behavioural features of the decision itself, such as rationality, complexity and anchoring. Our study highlights the relevance of the behavioural approach in reshoring decisions and provides evidence of many challenges that managers should be prepared to face. It further offers advice to policy makers, warning them about the dark side of reshoring and emphasizing their role in supporting companies to take structured rather than intuitive sub-optimal decisions. Highlights: Insights on how reshoring happens from a behavioural perspective. Different levels of complexity affect reshoring decision-making. High complexity is connected with flexible processes. The reshoring decision-making is intuitive in case of high complexity. An anchoring effect influence the reshoring decision-making.